Digestibility of feeds containing sorghum, with and without tannin, for broiler chickens submitted to three room temperatures - Garcia, R G [UNESP] (2004)
The traditional method of total excreta collection was applied, using 30 to 40 day old male Ross 308 broiler chickens. One hundred and eight broiler chickens were used, randomly assigned to a 3x3 factorial experimental design. The room temperatures were 14 C (cold), 25 °C (thermoneutral) and 32 °C (hot) and the three diets were 100% maize, 100% sorghum with tannin and 100% sorghum without tannin, with four replicates of each. The digestibility coefficients for the dry matter, crude protein, crude fibre, neutral detergent fibre, acid detergent fibre, ether extract, mineral matter and nitrogen-free extract were determined. It was observed that all the digestibility coefficients were higher in the hot chamber and lower in the cold chamber, and that these values tended to be higher for maize.